Revival Through Empo[women]t: Designing Safer Public Spaces in Post-Apartheid Communities that Promote Community Cohesion - Kanjee, Sanam D. (University of the Witwatersrand, Johannesburg, 2024)
This study investigates how architecture can transform and renew existing public realms in Downshops, Laudium. The space contains strong patriarchal culture, along with poor maintenance, dilapitated infrastructure, dark thresholds and polluted spaces. These factors have made the space very unwelcoming, uncomfortable and unsafe for women. Despite this, it contains multi-layered complexities of Post-Apartheid narratives regarding socio-economic status, religion, culture, race, gender, and languages that de昀椀ne the space. This study aims to revive underutilized infrastructure and increase female participation through environments that facilitate skills, knowledge, and economic opportunities for women. Architectural theories and themes guide the study by challenging conventional design norms, through inclusive design, safety methods, and materiality seen through the lens of women, that enhance women’s spatial experiences. Proposed design interventions celebrate women’s role in public spheres by including clean facilities, spaces of activity, a tea garden, daycare facilities, learning rooms, skills and craft markets, and a women’s market. A drop-o昀昀/pick-up zone and waiting area for taxis is also proposed. By re-imagining Downshops through a gender-sensitive approach, the study envisions clean, safe and welcoming environments that encourage women to be active participants in public spaces to promote empowerment and cohesive community living.
A research report submitted in fulfillment of the requirements for the Masters in Architecture, In the Faculty of Engineering and the Built Environment, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Revival; Safe Spaces; Community CohesionPost-Apartheid; SDG-11: Sustainable cities and communities